Small fibre pathology in chronic whiplash‐associated disorder: a cross‐sectional study - Farrell, SF; Sterling, M; Irving-Rodgers, H; Schmid, AB (Wiley, 2020)
Background Mechanisms underpinning ongoing symptoms in chronic whiplash associated‐disorder (WAD) are not well understood. People with chronic WAD can exhibit sensory dysfunction consistent with small nerve fibre pathology, including thermal hypoaesthesia and hyperalgesia. This study investigated small fibre structure and function in chronic WAD.